The Influence of Organizational Justice, Organizational Culture and Job Satisfaction on Organizational Commitment of Employees of the Health Department of Gunungkidul District - Azis, Muhammad Nur; Prayekti, Prayekti; Kusuma, Nala Tri (Universitas Muhammadiyah Makassar, 2025)
This study examines the influence of organizational justice, organizational culture, and job satisfaction on organizational commitment among employees of the Gunungkidul Regency Health Office. Using a quantitative approach, data were collected from a saturated sample of 80 employees through structured questionnaires measured on a Likert scale. The research variables included organizational justice, organizational culture, job satisfaction, and organizational commitment, adopted from established measurement instruments. Data analysis was conducted using multiple linear regression with SPSS. The results demonstrate that organizational justice has a positive and significant effect on organizational commitment, indicating that fair treatment in terms of workload, income, and recognition enhances employees’ willingness to remain dedicated to the organization. Similarly, organizational culture exerts a significant positive impact, suggesting that shared norms, values, and teamwork contribute to stronger commitment. Job satisfaction also positively influences commitment, showing that satisfied employees with supportive work environments are more likely to remain loyal. Furthermore, the simultaneous testing confirms that organizational justice, culture, and job satisfaction collectively explain 35.1% of the variance in organizational commitment, while the remaining 64.9% is attributed to other factors outside the study. The findings underscore the importance of promoting fairness, strengthening organizational culture, and ensuring job satisfaction to sustain employee commitment. This study contributes to the organizational behavior literature and provides practical recommendations for public institutions to enhance human resource management strategies in health sector organizations